2017
DOI: 10.1002/gamm.201720003
|View full text |Cite
|
Sign up to set email alerts
|

An electro‐elastic phase‐field model for nematic liquid crystal elastomers based on Landau‐de‐Gennes theory

Abstract: The present contribution proposes a continuum-mechanical phase-field approach to model the electro-elastic behavior of nematic liquid crystal elastomers. The nemato-electro-elastic model is embedded into the fundamental Landau-de-Gennes theory for isotropic-nematic phase transition and employs a tensorial order parameter as the phase field. Nematic deformations are incorporated through a constitutive ansatz in terms of the order parameter. The phase-field formulation is implemented into the finite element meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…More recently, Keip and Nadgir [ 128 ] proposed a continuum mechanics, phase-field method for modeling the electro-elastic behavior of nematic LCEs. The nemato-electro-elastic model is coupled with the Landau–de-Gennes theory and the phase field is described by using a tensorial order parameter.…”
Section: Other Numerical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Keip and Nadgir [ 128 ] proposed a continuum mechanics, phase-field method for modeling the electro-elastic behavior of nematic LCEs. The nemato-electro-elastic model is coupled with the Landau–de-Gennes theory and the phase field is described by using a tensorial order parameter.…”
Section: Other Numerical Methodsmentioning
confidence: 99%
“…This model contrasts with its predecessors [ 129 , 130 ] in that, it considers the full Landau–de-Gennes order parameter as phase field; therefore, allowing the new model to overcome the numerical challenges inherent in other director models [ 131 , 132 ]. A complete derivation of the mathematical framework used by the authors [ 128 ] can be found in the original manuscript. The authors’ results demonstrate that the proposed model was able to characterize how the nematic microstructures evolved to a good degree.…”
Section: Other Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current contribution, we discuss a rate-type variational homogenization framework for nemato-elastic solids. We refer to [4] for the employed phase-field model of nematic elastomers.…”
Section: Introductionmentioning
confidence: 99%